2021
DOI: 10.1177/2167702620978614
|View full text |Cite
|
Sign up to set email alerts
|

Motives for Substance Use in Daily Life: A Systematic Review of Studies Using Ecological Momentary Assessment

Abstract: The motivational model of substance use posits that four motive subtypes (coping, enhancement, social, conformity) dynamically interact with contextual factors to affect decisions about substance use. Yet prior studies assessing the motivational model have relied on between-persons, cross-sectional evaluations of trait motives. We systematically reviewed studies using ecological momentary assessment (EMA; N = 64) on motives for substance use to examine methodological features of EMA studies examining the motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 117 publications
(259 reference statements)
3
84
1
1
Order By: Relevance
“…According to theory, these associations should be stronger for people who self-report a disposition to drink-to-cope with negative emotions (coping motives) and drink-to-enhance positive emotions (enhancement motives), respectively (Hypotheses 2a + b) (Cooper et al, 1995). However, studies testing this hypothesized interaction have produced mixed results as well (Votaw & Witkiewitz, 2021), necessitating a meta-analytic model to evaluate the strength of evidence.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to theory, these associations should be stronger for people who self-report a disposition to drink-to-cope with negative emotions (coping motives) and drink-to-enhance positive emotions (enhancement motives), respectively (Hypotheses 2a + b) (Cooper et al, 1995). However, studies testing this hypothesized interaction have produced mixed results as well (Votaw & Witkiewitz, 2021), necessitating a meta-analytic model to evaluate the strength of evidence.…”
Section: Hypothesesmentioning
confidence: 99%
“…It may be that a person's self-report of dispositional motives reflects a mental model arising from formative drinking experiences, social cues and norms around the function of alcohol use, or from selectively recalled drinking events, rather than a description of a typical alcohol decision-making process for that person. Recent research has suggested that peoples' daily or momentary coping and enhancement motives for drinking are robust predictors of same day emotional drinking (Stevenson et al, 2019;Votaw & Witkiewitz, 2021). Other cognitive factors, such as cravings (Serre et al, 2015;Waddell et al, 2021), the momentary reinforcement value of alcohol (Murphy & Mackillop, 2006), and other drinking-related cognitions (Lewis et al, 2020) have been shown to vary within person and may be important for understanding how drinking motives are enacted to influence alcohol use in daily and momentary data.…”
Section: Implications For Motivational Models Of Alcohol Usementioning
confidence: 99%
“…For example, ecological momentary methods have been useful in exploring the relationship between alcohol use and related drinking motives and social context. Recent EMA studies report that drinking behavior in young adults is associated with daily motives to enhance mood, facilitate social interaction, and cope with negative affect (Votaw & Witkiewitz, 2021). In addition, Stevens et al (2021) found planned drinking specifically was associated with mood enhancement motives (e.g., drinking to get buzzed, see Stevens et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the motivational model of alcohol use (Cox & Klinger, 1988) considers positive and negative incentives in its theoretical framework and suggests incentives specific to a situation play a major role in expectancies, motives, and affect related to drinking (see Cox & Klinger, 1988). Indeed, a rich body of literature has examined motives of substance use (Bresin & Mekawi, 2021; Cox & Klinger, 1988; Votaw & Witkiewitz, 2021) which primarily reflect personal reasons to drink (Cooper, 1994) while not always considering decision incentives that may reflect event ‐specific reasons to decide to drink or attend a drinking event. For example, research of drinking motives typically asks participants “How frequently is your drinking motivated by the following reasons?” or “Please rate how important each item is to you as a reason for drinking” (Cooper, 1994; Votaw & Witkiewitz, 2021), which do not fully assess the influence and varying presence of event‐specific incentives on the participant's decision to drink as originally theorized by Cox and Klinger (1988).…”
Section: Introductionmentioning
confidence: 99%
“…Among U.S. college students, past‐year alcohol (75%) and cannabis (42%) use are common (Schulenberg et al, 2020) and linked to substantial negative outcomes, including academic issues, physical and/or sexual assault, and psychosocial problems (Hingson et al, 2017; Pearson et al, 2017; Simons et al, 2012). Decades of research have studied the reasons why individuals drink or use cannabis (see Cooper et al, 2016; see also Votaw & Witkiewitz, 2021). However, less research has focused on a person's reasons for nonuse or their decision to not use any substance on a given day when use was originally planned, which has significant implications for enhancing alcohol‐ and cannabis‐related harm reduction.…”
Section: Introductionmentioning
confidence: 99%